Ontogenetic view on PIVKA-II in the development of prothrombin synthesis in infants - O. G. Ivanko; A. V. Solianik; I. V. Pashchenko (Zaporozhye State Medical University, 2017)
The aim of the research was to study the content of PIVKA-II in the blood serum as an integrative measure of latent vitamin K deficiency in breastfed infants aged from the birth to 6 months of life. Materials and methods. 178 children aged from the birth to 6 months of life who were born without birth injuries in the term of 38-41 of weeks gestation with a weight 2800-4200 g were examined. The immunoenzyme assay for PIVKA-II study was performed with ANTIBODY RESEARCH kit PIVKA-II ELISA Kit (USA) Results. Children who had not received postnatal prophylactic injection of vitamin K1 in dose of 1 mg intramuscularly in their majority (62 %) had abnormally elevated serum PIVKA-II (>40 Au/ml) at the first week of life. In 92 % of children who had received a prophylactic dose of vitamin K1 immediately after birth, PIVKA-II was in a normal limit. The normal concentrations of PIVKA-II were observed in children aged 2-6 months regardless of vitamin K prophylactics. The situation worsened dramatically in children who were treated with antibiotics because more than 50 % of these children have experienced high PIVKA-II values. Conclusions. Almost all the children in their first week of life whom for any reasons vitamin K1 was not prescribed have exhibited an elevation of PIVKA-II in blood serum. This indicates an inborn deficiency of vitamin K experienced by fetuses and newborns. Prophylactic injection of vitamin K1 to newborns normalizes the processes of prothrombin carboxylation and PIVKA-II concentrations are getting normal. Children, who did not receive vitamin K1 after the birth, during the first month of life spontaneously normalize the PIVKA-II concentrations. The improvement of prothrombin carboxylation is obviously connected with the colon microbiota development which can provide children with well absorbed vitamin K2 (menaquinone). In 55.5 % of breastfed children aged up to 6 months who had received antibiotics the PIVKA-II appeared elevated again. This indicates the renewal of the vitamin K deficiency in conditions of the colon microbiota damage.